(untitled) (Journal of Economic Research & Business Administration, 2015)
Innovative development of economy is considered today by many countries as one of the main ways of economic growth, ensuring competitiveness. The most discussed questions of innovations in the Republic of Kazakhstan are: institutes, finance, regulation, shots, technologies, intellectual property rights. Such rather new aspect of research as open innovations, can become the integral element in the mechanism of realization of Strategy of industrial and innovative development of Kazakhstan. In spite of the fact that studying of questions of innovative development was widely adopted at us in the country, the problem of open innovations is the new direction which has appeared recently in foreign literature. In this article the essence of new approach in management of innovative activity, namely application of model of open innovations for maximizing profit of the company reveals. Also comparison of the principles of traditional innovative management with the principles of management on the basis of open innovations is given that in turn leads to an explanation of trends of management on the basis of model of open innovations.